Strategi Pengembangan Bahan Ajar Al-Qur’an Hadis pada Era Digital di MTs Yapika Petanahan Kebumen - Kissti Lailatul Fajriyyah; Sofan Rizqi; Nasokhah Nasokhah (Reflection : Islamic Education Journal, 2025)
This study aims to identify the strategies implemented by Al-Qur'an Hadith subject teachers in developing teaching materials in the digital era at MTs Yapika Petanahan Kebumen. In addition, this study also examines the factors that support and inhibit the development of digital teaching materials by teachers. The method used in this study is qualitative with interview and observation techniques. The results show that the strategies implemented include the use of modern technology, multimedia integration, creation of digital teaching materials, use of digital learning platforms, and evaluation. Supporting factors in the development of teaching materials include a wide internet network, student habits in using digital tools, and support from school leaders. Conversely, inhibiting factors consist of inadequate facilities, limited access to electricity in some classes, and the majority of students living in Islamic boarding schools.